Mindfulness as a key mechanism: linking flow and emotional intelligence to academic engagement in Chinese university students - Wu, You; Ma, Rui (Frontiers in Psychology, 2025)
IntroductionThis study investigates the interrelationships among academic flow, trait emotional intelligence (EI), and mindfulness as predictors of academic engagement among Chinese university students. We explore these dynamics at both trait and momentary state levels, a gap in the existing literature.MethodsA multi-phase mixed-methods design was employed. The initial phase involved quantitative surveys with 394 university students. A subset of 30 students participated in qualitative focus group discussions, followed by an Experience Sampling Method (ESM) phase with 80 students over 7 days. Data were analyzed using structural equation modeling (SEM) for the survey data, multilevel modeling (MLM) for the ESM data, and thematic analysis for the qualitative data.ResultsSEM results showed that trait academic flow and trait EI had significant positive direct effects on academic engagement. Importantly, trait mindfulness emerged as a significant mediator of both these relationships, with the full model explaining 62% of the variance in engagement. MLM of the ESM data revealed that momentary mindfulness positively predicted subsequent increases in momentary academic flow and engagement. Additionally, higher trait EI was found to buffer the negative impact of momentary stress on real-time engagement. Thematic analysis of the focus groups provided rich contextual insights that supported these quantitative findings.ConclusionThe combined findings demonstrate that mindfulness is a critical psychological mechanism linking flow and emotional intelligence to academic engagement, functioning both as a stable disposition and a dynamic state. This multi-level evidence suggests that interventions aimed at enhancing mindfulness could be highly effective in fostering greater student engagement and success in higher education.